Integralidade do cuidado na utilização de serviços de atenção primária à saúde por adultos - Rosa, Fabio Mello da (2018)
Primary Care, as a level of the health system responsible for the entry of all the new needs and problems of the population and for the organization of an integrated health system, presents exclusive functions within the health system, as well as its own attributes. attention to first contact, longitudinality, coordination of care and completeness. One of the instruments of health evaluation, which plays the role of quantitatively measuring the quality of health services based on the attributes of PHC, is the Primary Care Assessment Tool Brazil version. The objective of this study was to analyze the prevalence and associated factors of the integrality of care perceived by adults in the primary health care services of the 32 municipalities that compose the 4th Regional Health Coordination / RS in 2015 and to obtain the bibliometric indicators on the instrument results for Primary Care Assessment Tool in Brazil. This is a cross-sectional observational epidemiological study (municipalities and individuals). The study population was composed of adults from the 32 municipalities belonging to the region of the 4th Regional Health Coordination (CRS). The data collection was performed using the Primary Care Assessment Tool - Brazil, validated in its adult version, plus a questionnaire with socioeconomic and demographic information. Data were analyzed in Stata 11 software. Analyzes of the absolute and relative frequencies of the studied variables were performed. The ethical precepts respected Resolution 466/2012. In the first article, 149 studies were retrieved in the LILACS, PubMed, SCOPUS and WoS databases, which allowed to know the incidence of studies by year of publication, PCATool version, attributes, application scenarios and the origin of the institutions. The areas of multiprofessional knowledge, the number of authors, the qualification of the first author, the key words, the type of study, other instruments, periodicals and the impact factor were identified. In the second article, the highest prevalences of completeness were found in small municipalities, with higher per capita GDP, in the Entre Rios region and with up to 28.6% of ICSAB. Regarding the individual characteristics, the highest prevalences were among female adults, 80 years of age or older, not literate, unemployed and using units. It was evidenced, especially in Primary Health Care, that the use of the PCATOOL instrument is adequate to evaluate the presence and extension of the essential attributes and derivatives. The measurement of these contributes so that the municipal and regional health managers can carry out the planning of the public policies of more secure way to the extent that it subsidizes the evaluation of the actions that are being carried out in the territory. By pointing out the potentialities and / or weaknesses of services, it signals the reorientation of health care practices. It is understood that more longitudinal studies and evaluative surveys are needed that incorporate contextual factors in the health services and, therefore, evaluation of other characteristics of the municipalities beyond those presented in this study.